2019
DOI: 10.3389/fnins.2019.00832
|View full text |Cite
|
Sign up to set email alerts
|

Functional Frequency Discrimination From Cortical Somatosensory Stimulation in Humans

Abstract: Recently, efforts to produce artificial sensation through cortical stimulation of primary somatosensory cortex (PSC) in humans have proven safe and reliable. Changes in stimulation parameters like frequency and amplitude have been shown to elicit different percepts, but without clearly defined psychometric profiles. This study investigates the functionally useful limits of frequency changes on the percepts felt by three epilepsy patients with subdural electrocorticography (ECoG) grids. Subjects performing a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
2
1
Order By: Relevance
“…We found that a frequency difference of 10 Hz led to a poor accuracy of 16.7%, whereas a frequency difference of 30 Hz led to a greatly improved accuracy of 85.7%. Previously, we have shown that a 10-Hz difference, between 20 and 100 Hz, is detected above chance; 15 however, here 10 Hz or smaller differences occurred at lower tested frequencies (2, 5, 10, or 20 Hz). These results likely reflect a lower detection threshold of around 20 Hz, rather than a just-noticeable difference.…”
Section: Figcontrasting
confidence: 61%
See 1 more Smart Citation
“…We found that a frequency difference of 10 Hz led to a poor accuracy of 16.7%, whereas a frequency difference of 30 Hz led to a greatly improved accuracy of 85.7%. Previously, we have shown that a 10-Hz difference, between 20 and 100 Hz, is detected above chance; 15 however, here 10 Hz or smaller differences occurred at lower tested frequencies (2, 5, 10, or 20 Hz). These results likely reflect a lower detection threshold of around 20 Hz, rather than a just-noticeable difference.…”
Section: Figcontrasting
confidence: 61%
“…We have previously shown that 10-Hz differences are detectable between 20 and 60 Hz but did not explore lower, or repeat, frequency stimulations to assess the threshold of absolute detection to inform stimulation parameters in BCI. 15 Here, we show that repetitive stimulation with the same two frequencies is easily distinguishable, suggesting the stability of frequency as a stimulation "degree of freedom" for somatosensory BCI. In the second paradigm, when one stimulus was 50 or 100 Hz, accuracy was 91.7%, compared with 40.7% when both stimuli were less than or equal to 20 Hz (p < 0.001).…”
Section: Figmentioning
confidence: 59%
“…For the second aspect, a common practice is to apply electric stimulation on the surface of the cortex. Previous research has demonstrated that human participants can discriminate the perceptual intensity elicited with either varied frequency or varied amplitude using both ECoG [170]- [175] and SEEG [176]. Despite these results, many issues still exist that have complicated the implementation of artificial sensation in BCIs.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%